IMPLEMENTASI TANGGUNG JAWAB SOSIAL PERUSAHAAN DALAM BENTUK PROGRAM KEMITRAAN DAN BINA LINGKUNGAN - Chandra Dewi Puspitasari (Jurnal Penelitian Humaniora, 2012)
This study is aims to determine the implementation of corporate social responsibility in the form of “Program Kemitraan dan Bina Lingkungan (PKBL) at PT Madubaru and the obstacles, and to determine the impact of the implementation of corporate social responsibility, both for companies and for local communities who were targets PKBL. This study is a descriptive study with qualitative approach. Subject of study is determined by purposive and snowball technique. The data was collected by interviews and document studies. Furthermore, the data were analyzed using inductive analysis. The results suggest that corporate social responsibility that is implemented is still largely in the form of momentary fulfillment, not to the aspect of sustainability as intended in community development. Obstacles encountered in implementing PKBL is difficult to find small businesses that fit with the company's business activities, the difficulty of finding good business-minded and responsible, and not compatibles PKBL budget allocation for the activity by the number of requests, so the funds are rolled still considered small by the community. The impact of the implementation is not optimal PKBL felt, because, although PT Madubaru has implemented PKBL in various activities and felt there was a good relationship with the local community that is created through the implementation PKBL, but on the other side of the perceived benefit of trained partners and target communities to the extent not empower society